A Case Report of Anal Mucocellular Carcinoma Assosiated with Perianal Paget's Disease - Kawai, Masami; Isogai, Masatoshi; Kin, Yukoh; Yamada, Tatsuharu; Kubota, Tomoyuki; Yamaguchi, Akihiro; Hori, Akihiro; Takano, Manabu; Yamaguchi, Ryuzo; Maeda, Atsuyuki (Nippon Shokaki Geka Gakkai zasshi, 1995)
Perianal Paget's disease is rare. Only twenty cases, including ours, have been reported in Japan, and almost all of them have been associated with malignant tumors. We describe one case of Paget's disease with anal cancer originating from anal glands. A 79-year-old man came to our hospital with chief complaints of anal tumor and bleeding. We found an anal tumor on the dentate line and perianal erosion. Biopsy of the anal tumor reveraled signet ring cell carcinoma, and abdominoperineal resection was performed. Histologically, the anal tumor was mucocellular carcinoma with mucous lake, and the perianal erosion was due to the intraepidermal spread of signet ring cells, i.e., Paget's cells. Based on the literature, we report that perianal Paget's disease shows a relationship with anaI cancer originating from anal glands.